Reliable and reconfigurable computing research under SUG14/06 - Mcloughlin, Ian. (2010)
The central thesis of this research is toward the concept of reliability through redundancy for computational systems: in order to achieve a sufficiently fault-tolerant system, given sufficiently many computers an a sufficiently reliable connection strategy, there exists an arrangement that will satisfy the fault tolerance requirement. This research aims to advance the state of knowledge in this field, and primarily to build and test examples of real systems. We have constructed and tested hardware, systems, simulated system, experimented with high-altitude flight for satellite computers, and built most of a reliable nanosatellite.